2011
DOI: 10.3892/or.2011.1274
|View full text |Cite
|
Sign up to set email alerts
|

Ectonucleoside triphosphate diphosphohydrolase 6 expression in testis and testicular cancer and its implication in cisplatin resistance

Abstract: Abstract. the development of resistance to cisplatin during treatment of testicular cancer constitutes a major obstacle to the cure of testicular cancer. to resolve its mechanism will provide useful information for making clinical decisions. We found 4 and 15 gene expressions were, respectively, up-regulated and down-regulated in cisplatin-resistant testicular cancer nec-8/DDp cells compared with their parental nec-8 cells (about 2.5-fold) using cDnA microarray analysis. After screening, we selected the entpD6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Cisplatin is one of most commonly used chemotherapeutic drugs in the treatment of solid tumors including liver [1], lung [2], breast [3], cervical [4], ovarian [5], and testis [6] cancers. Although cisplatin has been shown to be one of the most effective anticancer drugs, its use in clinical application is limited because of its side effects in normal tissues [79].…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is one of most commonly used chemotherapeutic drugs in the treatment of solid tumors including liver [1], lung [2], breast [3], cervical [4], ovarian [5], and testis [6] cancers. Although cisplatin has been shown to be one of the most effective anticancer drugs, its use in clinical application is limited because of its side effects in normal tissues [79].…”
Section: Introductionmentioning
confidence: 99%
“… 35 Tada et al have demonstrated that ENTPD6 monitors cisplatin resistance in testis and testicular cancer. 36 Rosin et al have found that DYX1C1 can indicate the poor survival in breast cancer. 37 How FCF1 and TBC1D22A act in CESC is waiting to be answered by future research.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that the modulation of NTPDase expression might contribute to resistance development; however, this finding should be further investigated. The role of the NTPDases in the development of resistance has been poorly explored in the literature; however, in cisplatin-resistant testicular tumor cells (NEC-8/DDP), the expression of ENTPD6 was found to be decreased [39].…”
Section: Discussionmentioning
confidence: 99%